1982
DOI: 10.1007/bf00133291
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of nodulation in Chickpea (Cicer arietinum L.)

Abstract: Combining ability, components of genetic variance and graphic analysis revealed that nodulation in the cultivars of Chickpea (Cicer arietinum L.) under study, was predominantly under the control of non-additive gene action although substantial additive effect was also present. The crosses giving high specific combining ability effects also manifested highly significant positive heterosis. The parents F-61, Giza and Annegiri possessed mostly dominant alleles while Phule G-5, NEC-249 and N-3 1 possessed mostly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…For example, predominant non-additive genetic variation accounts for nodule number, nodule weight, nitrogenase activity, and shoot weight in cowpea (Miller et al, 1986), while non-additive genetic variation explains nodule number and shoot weight, and additive genetic variation for nodule weight in common bean (Franco et al, 2001). Likewise, predominant non-additive genetic variation was important for nodule number in chickpea (Bhapkar and Deshmukh, 1982), while predominant additive genetic variance was significant for nodule number, nodule weight, shoot weight, total nitrogen, percentage of N derived from atmosphere and nitrogen fixed per plant in mungbean (del Rosario et al, 1997). In groundnut, predominance of both additive and non-additive genetic effects and evidence of epistatic interactions are reported.…”
Section: Qtl Associated With Snf Traitsmentioning
confidence: 99%
“…For example, predominant non-additive genetic variation accounts for nodule number, nodule weight, nitrogenase activity, and shoot weight in cowpea (Miller et al, 1986), while non-additive genetic variation explains nodule number and shoot weight, and additive genetic variation for nodule weight in common bean (Franco et al, 2001). Likewise, predominant non-additive genetic variation was important for nodule number in chickpea (Bhapkar and Deshmukh, 1982), while predominant additive genetic variance was significant for nodule number, nodule weight, shoot weight, total nitrogen, percentage of N derived from atmosphere and nitrogen fixed per plant in mungbean (del Rosario et al, 1997). In groundnut, predominance of both additive and non-additive genetic effects and evidence of epistatic interactions are reported.…”
Section: Qtl Associated With Snf Traitsmentioning
confidence: 99%
“…Genotypic variation for nodule formation ability (nodule number and nodule dry weight) and N2 fixation ability was found in clover (Nutman, 1967), common bean (Phaseolus vulgaris L.) (Chavera and Graham, 1992;Montealegre et al, 1994), soybean (Videira et al, 2001) chickpea (Romdhane et al, 2007). Using diallel cross populations, it also has been shown that nodule formation ability is under polygenic control, in which non-additive gene action as well as substantial additive effect was presented (Bhapkar and Deshmukh, 1982). Cultivars response to inoculation with diverse rhizobial strains also has been studied in several leguminous plants.…”
Section: Introductionmentioning
confidence: 99%